FACTORS AFFECTING HEALTH WORKERS’ ENGAGEMENT IN PUBLIC HOSPITAL - Tita Miawati; Didik Notosudjono; Widodo Sunaryo (UNIVERSITAS PAKUAN, 2022)
Many researches of employee engagement proved that engagement is an important factor in providing successful quality services in hospital. Engaged health workers who are energized, loyalty, dedicated, absorbed in their work have an important role in accelerate patient healing, tackling the shortage of health workers and sustainable cost efficiency. The purpose of this study is to find out the effect of organizational culture and servant leadership on health workers engagement in public hospital. The survey method design was used in the study to a public hospital in Tasikmalaya city, Indonesia. The Likert-scale questionnaires was used to measure the strength of 75 health workers’ engagement, organizational culture and servant leadership. The study had generated finding that the public hospital culture and the servant leadership of health workers have significant and positive effect to the health workers’ engagement. In addition, the effect of servant leadership was stronger than the organizational culture. Based on the result of research, it is necessary to develop servant leadership qualifications by increasing the spirit of supervisor service and fostering work-values based culture of the hospital to improve health workers’ engagement.